2020
DOI: 10.1272/jnms.jnms.2021_88-501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Gene Expression of Beating Neonatal Rat Cardiomyocytes - Further Research with Ingenuity Pathway Analysis Software -

Abstract: Background: There have been no comprehensive investigations that examined the alteration of heart gene expression due to ethanol exposure. Therefore, we attempted to obtain gene expression from cultured neonatal rat cardiomyocytes exposed to ethanol (0, 10, 50, 100 mM) for 24 h. Methods: The total RNA extract of beating cardiomyocytes was evaluated using DNA microarray, and fold changes (FCs) of differential gene expression of ethanol-exposed cardiomyocytes were analyzed against the control using Ingenuity Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
0
4
0
7
Order By: Relevance
“…A recent study on the prognosis markers of glioblastoma revealed the expression of ASIC5 as associated prognosis markers (55). ASIC5 was found to be activated in the ethanol-(100 mM)-exposed neonatal rat cardiomyocytes along with other six molecules (CYP2A6, PRL, CHRNA4, CNR1, CRH, and SLC40A1) (56). Low (in 50%) ASIC5 protein expression in melanoma were observed with <4% mutation rates (57).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study on the prognosis markers of glioblastoma revealed the expression of ASIC5 as associated prognosis markers (55). ASIC5 was found to be activated in the ethanol-(100 mM)-exposed neonatal rat cardiomyocytes along with other six molecules (CYP2A6, PRL, CHRNA4, CNR1, CRH, and SLC40A1) (56). Low (in 50%) ASIC5 protein expression in melanoma were observed with <4% mutation rates (57).…”
Section: Discussionmentioning
confidence: 97%
“…Попередні дослідження показали, що аутофагія також може бути механізмом кардіотоксичності етанолу за рахунок протеїнкінази, активованої аденозинмонофосфатом, з подальшим ушкодженням метаболізму глюкози та ліпідів [11]. У морфологічних і молекулярно-біологічних дослідженнях доведено, що тривала дія етанолу пригнічує синтез і викликає деградацію структурних білків кардіоміоцитів, особливо білків міофібрил -актину, міозину, тітину, небуліну, тропоніну, тропоміозину [4,16,21]. Це призводить до ушкодження міофібрил, їх стоншення, дезорієнтації, втрати цілісності, спотворення конфігурації телофрагм та вставних дисків [2,16].…”
Section: вступunclassified
“…У морфологічних і молекулярно-біологічних дослідженнях доведено, що тривала дія етанолу пригнічує синтез і викликає деградацію структурних білків кардіоміоцитів, особливо білків міофібрил -актину, міозину, тітину, небуліну, тропоніну, тропоміозину [4,16,21]. Це призводить до ушкодження міофібрил, їх стоншення, дезорієнтації, втрати цілісності, спотворення конфігурації телофрагм та вставних дисків [2,16]. Показано, що в кардіоміоцитах за умов дії етанолу можна визначити міофібрили як у релаксованому, так і в надмірно скороченому стані [6,22].…”
Section: вступunclassified
See 1 more Smart Citation
“…Ingenuity pathway analysis (IPA) is a powerful tool with multipurpose solutions for the interpretation, and the analysis of complicated experimental datasets ( 8 ). It has also been used by many scientific research institutions ( 9 ), including medical, pharmaceutical, and biotechnological institutions, among others. Based on this, iTRAQ quantitative proteomics associated with IPA analytical tool can offer a credible biological analysis of RA ( 10 ) by comparing different groups, especially could help us to reveal the key up-regulated or down-regulated DEPs.…”
Section: Introductionmentioning
confidence: 99%